Cover. Issue 10 (9th October 2017) - Joda, Tim; Lenherr, Patrik; Dedem, Philipp; Kovaltschuk, Irina; Bragger, Urs; Zitzmann, Nicola U.
Abstract : The cover image, by Tim Joda et al., is based on the Original Article Time efficiency, difficulty, and operator's preference comparing digital and conventional implant impressions: a randomized controlled trial, DOI:10.1111/clr.12982 .